Transformational leadership style and its role in promoting innovation: A Case study of three public hospitals in Egypt - El Fiky, Ragaa (AUC Knowledge Fountain, 2016)
This study investigates the transformational leadership style and its role in promoting employees' innovation. The study uses a mixed method approach; quantitative and qualitative analysis. To confirm the outcomes of the collected and analyzed data, a qualitative research was conducted via in-depth and descriptive analysis of the proposed correlation. Survey and interview were conducted in three public hospitals located in Cairo, Mansoura and Damietta, Egypt. Findings of quantitative and qualitative analysis strongly supported the main question of the study that transformational leadership style has a relationship and a role in promoting employees' level of innovation which was suggested in the adopted conceptual framework. Results confirmed that the three sub-questions of this research supported the main proposed question. Measures were found to be positively associated with the five proposed hypotheses and were proven to be effective on employees' innovation with a correlation of some external factors such as: "clear vision and mission","lead by doing rather by telling", "innovative leader", "empowerment", "motivation", and "being valued".